2022
DOI: 10.3389/fendo.2022.945609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin versus metformin plus liraglutide on gonadal and metabolic profiles in overweight patients with polycystic ovary syndrome

Abstract: ObjectiveTo observe the effect of metformin (MET) monotherapy versus MET plus liraglutide (LIRA) on gonadal and metabolic profiles in overweight patients with polycystic ovary syndrome (PCOS).MethodsSixty overweight patients with PCOS were recruited from January 2021 to January 2022 in Shengjing Hospital of China Medical University and were randomly assigned to the MET or combination (COM) group to receive 12 weeks of MET monotherapy or MET plus LIRA therapy. Anthropometric measurements, menstrual cycle change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
(49 reference statements)
1
20
1
Order By: Relevance
“…found that after 24 weeks of therapy with the combination of exenatide and MET, the TT levels also considerably reduced ( 9 ). This result differed from that of Chuan Xing et al ( 29 )and Liu et al ( 40 ), who randomized overweight/obese PCOS patients to receive exenatide or liraglutide combined with MET versus MET alone for 12 weeks and found that neither group saw a clear decrease in the TT levels. There is now widespread agreement that the most sensitive indicator of hyperandrogenaemia is blood concentrations of free testosterone, which exerts biological effects on tissues not by TT ( 41 ), And sex hormone-binding globulin (SHBG) as a marker of IR and metabolic complications in PCOS is widely advocated ( 15 ).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…found that after 24 weeks of therapy with the combination of exenatide and MET, the TT levels also considerably reduced ( 9 ). This result differed from that of Chuan Xing et al ( 29 )and Liu et al ( 40 ), who randomized overweight/obese PCOS patients to receive exenatide or liraglutide combined with MET versus MET alone for 12 weeks and found that neither group saw a clear decrease in the TT levels. There is now widespread agreement that the most sensitive indicator of hyperandrogenaemia is blood concentrations of free testosterone, which exerts biological effects on tissues not by TT ( 41 ), And sex hormone-binding globulin (SHBG) as a marker of IR and metabolic complications in PCOS is widely advocated ( 15 ).…”
Section: Discussioncontrasting
confidence: 88%
“…It seems that weight loss could be beneficial to clinical(reproductive and metabolic) outcomes in PCOS patients ( 26 , 27 ). Although many studies have confirmed the weight reduction effects of metformin and GLP-1RA ( 15 , 28 , 29 ), the potential action of beinaglutide combined with metformin versus metformin alone on weight loss in PCOS has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects still deserve a greater insight, especially in the light of a possible therapeutic use in PCOS women independently of obesity. Contrariwise, other relevant aspects, such as the safety profile and tolerability of GLP-1RA or the beneficial effects on fertility in PCOS, have been more extensively treated, especially considering that possible direct or indirect reproductive effects of GLP-1 RA might require a concomitant effective contraception and a washout period before pregnancy [22,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%